O aprender do bebê : representações sociais segundo acadêmicos de Pedagogia da UFMT, Campus Cuiabá - Cavallari, Sandra Aparecida (2012)
The present study attempts to identify the content and structure hypothesis of social representations about the baby and the baby learning, according the four undergraduate years of the Faculty of Education, Federal University of Mato Grosso (UFMT), Cuiabá campus. The theoretical approach adopted is the Theory of Social Representations (MOSCOVICI, 1978, 2003; JODELET, 2001) and the Theory of Central Nucleus (ABRIC, 1998). It also was based on studies of childhood according Chombart Lauwe (1991) and Sarmento (2007), in addition to the assumptions about development and learning of Oliveira, M. K. (2010), Oliveira Z. M. (2001), Freitas (1998), Goulart (1995) and Rappaport, Fiori, Davis (1981). The work focuses on analyzing evocations of the inducer term baby and the expression baby learning, accoording 213 scholars.The data were processed by the computer program Programmes Permettant Ensemble l'Analyse des Évocations (EVOC), considering the average order of evocation (OME) and the average order of importance (OMI).The relationship implied between the words evoked was analyzed from the processing software Classification Hiérarchique Implicative et Cohésitive (CHIC), to identify possible ways of thought. Scholars represent the baby anchoring it in the idea of affection through the outstanding care in the first year of life by the attitude of the adult continence objectified image of the mother. The baby is represented by the notion of incompleteness, passivity, dependency and development. The representation on the baby is learning from its relationship with the idea of development, now understood according to notions of perspective interactionist and sociointeracionista, or as stimulated by a natural way of affection, probably attributed to the maternal figure. Observed silencing of content related to Early Childhood Education, and the adult-child relationship in family context more salient aspect of the representational field in question. The results indicate that for the academic pedagogy, pedagogical work with babies is not presented as a possibility for action.